Examining the role of entrepreneurial universities in regional development - Daniel, Ana Dias; Teixeira, Aurora Amélia Castro; Preto, Miguel Torres (IGI Global, 2020)
"This book examines the role of entrepreneurial universities on regional development and on the promotion of local entrepreneurial ecosystems"--
Keywords: Business incubators; Entrepreneurship; Community development